Morphological Analysis of Gay’s Spoken Discourse - Lunzaga, Ariel B.; Bendulo, Hermabeth O.; Lunzaga, Ariel B. (JPAIR Multidisciplinary Research, 2011)
The language of gays known as Gay speaks has now earned respect from the community and observably been infused in the mainstream language of the society. Language is evolving and with its changing nature, existing language needs to be documented for posterity reasons. Gay speak is not an exemption. It has to be analyzed especially its morphology. This study focused on the morphological analysis of the language of gays who were studying at SLSU-Tomas Oppus in SY 2009-2010. Specifically, it identified the common vocabulary of local gays and the corresponding meanings through a self-administered questionnaire and an informal conversation. Based from the information provided by 20 purposively selected college gays, it was learned that gayspeak is simply an adaptation of the mainstream language like English, Filipino, and Cebuano. For purposes of hielding from the chasms of the heterosexuals, gays construct their language through simple reversal, syllabic reversal, simple reversal with affixation, clipping with affixation, straight words with affixation, and connotation through images. It was concluded that the spoken discourse of college gays in the campus violates the rules of English grammar yet used by gays for purposes of expressing themselves in a way unrecognizable by the discriminating straight men in highly patriarchal society.